Pengaruh Implementasi Sistem Informasi Manajemen Rumah Sakit Terhadap Kinerja Karyawan: Tinjauan Literatur - Triana, Meutia Hafni Indah; Purba, Sri Hajijah; Panggabean, Diani Sari; Sari, Fhidiana (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Hospital Management Information System (SIMRS) is an information technology designed to manage the entire process of health services in an efficient and integrated manner. SIMRS implementation plays an important role in supporting decision making, increasing work efficiency, and improving the quality of hospital services. The purpose of this study is analyze the effect of SIMRS implementation on employee performance in the health sector. The method used is a The study employs a literature review methode by national research articles published between 2017-2024. Data sources were obtained through the Google Scholar database with keywords related to hospital management information systems and employee performance. The data was analyzed based on research results from several relevant journals. The results showed that SIMRS implementation has a significant influence on hospital employee performance. SIMRS is proven to improve operational efficiency, data accuracy, and speed in health services. The majority of studies reviewed showed a significant relationship between SIMRS and improved employee performance, as indicated by a significance value of p < 0.05 in various studies. SIMRS implementation has a positive impact on employee performance, both in terms of work effectiveness and quality of health services.